Holes - Sachar, Louis 1954- (Farrar, Straus and Giroux, 1998)
As further evidence of his family's bad fortune which they attribute to a curse on a distant relative, Stanley Yelnats is sent to a hellish correctional camp in the Texas desert where he finds his first real friend, a treasure, and a new sense of himself.